The combination of fluoxetine and environmental enrichment reduces postpartum stress-related behaviors through the oxytocinergic system and HPA axis in mice - Hamideh Bashiri (Nature Portfolio, 2021)
Abstract Gestational stress can increase postpartum depression in women. To treat maternal depression, fluoxetine (FLX) is most commonly prescribed. While FLX may be effective for the mother, at high doses it may have adverse effects on the fetus. As environmental enrichment (EE) can reduce maternal stress effects, we hypothesized that a subthreshold dose of FLX increases the impact of EE to reduce anxiety and depression-like behavior in postpartum dams exposed to gestational stress. We evaluated this hypothesis in mice and to assess underlying mechanisms we additionally measured hypothalamic–pituitary–adrenal (HPA) axis function and brain levels of the hormone oxytocin, which are thought to be implicated in postpartum depression. Gestational stress increased anxiety- and depression-like behavior in postpartum dams. This was accompanied by an increase in HPA axis function and a decrease in whole-brain oxytocin levels in dams. A combination of FLX and EE remediated the behavioral, HPA axis and oxytocin changes induced by gestational stress. Central administration of an oxytocin receptor antagonist prevented the remediating effect of FLX + EE, indicating that brain oxytocin contributes to the effect of FLX + EE. These findings suggest that oxytocin is causally involved in FLX + EE mediated remediation of postpartum stress-related behaviors, and HPA axis function in postpartum dams.